Anti-Oxidative and Anti-Inflammatory Effects of Phenolic Compounds from the Stems of Quercus acuta Thunberg - Oh, M.H.; Park, K.H.; Kim, M.H.; Kim, H.H.; Kim, S.R.; Park, K.J.; Heo, J.H.; Lee, M.W. (Asian Journal of Chemistry, 2014)
Two flavan 3-ols i.e., (+)-catechin (1), (-)-epicatechin (2)], three flavanonols i.e., [taxifolin (3), taxifolin 3-O-b-D-glucopyranoside (4) and taxifolin 4'-O-b-D-glucopyranoside (5), one proanthocyanidin i.e., procyanidin B-3 (6) and one i.e., neolignan (+)-lyoniresinol 3a-O-b-D-xylopyranoside (7) have been isolated from the stems of Quercus acuta Thunberg (QAS) by anti-oxidative activity-guided isolation. Although these compounds have been reported previously. To our best of knowledge, this is the first study to report their isolation from Q. acuta Thunberg. Anti-oxidative activity was measured using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical and superoxide dismutase (SOD)-like superoxide anion (generated by xanthine oxidase/hypoxanthine) scavenging assays. Anti-inflammatory activity was assessed by quantifying the nitric oxide in the supernatant of lipopolysaccharide (LPS)-stimulated mouse Raw 264.7 macrophage cells.